ENHANCE STUDENT UNDERSTANDING ENGLISH BASED ON READING ALOUD - Ulpah Maisari; Atma Jonar Asih; Ely Ezir (Jurnal Scientia, 2023)
This paper discussed study Implementation of reading aloud learning strategies in increasing VB grade students' understanding of English material at SDN Klambir V Hamparan Perak and a method used in this study is a qualitative descriptive method, which is a method for describing the data that has been collected clearly and in detail as it is. Meanwhile, data collection techniques using data analysis were carried out through the stages of observation, interviews, documentation and data sources for students, teachers, VB homeroom teachers and administration. The results of this study are to increase students' understanding in the learning process and teach students to be more active in following a subject, especially PAI lessons, where this strategy is used in active learning and can support the achievement of good grades for students. The constraints experienced in the learning process by using the reading aloud strategy provide an interesting thing.